1994
DOI: 10.1557/proc-345-93
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Thermal Crystallization Of LPCVD Amorphous Silicon Films

Abstract: The crystallization of LPCVD a-Si by Rapid Thermal Anneal was investigated. RTA polysilicon films can find application in the fabrication of TFTs for AMLCDs, due to the lower thermal budget associated with fast crystallization at high temperatures. It was found that the grain size of the crystallized films decreases with the temperature, in the range of 700°C to 1100°C, while for higher temperatures the opposite trend is observed. The latter observation was attributed to the high thermal vibration of subcritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Because the rate of nucleation has a higher activation energy than the rate of crystal growth [20,21,22], raising the crystallization temperature above 600°C increases the number of nuclei, reduces their size, and reduces the field effect mobility [25]. Somewhere above 850°C the nucleation rate is expected to drop while the growth rate keeps rising [20], so that at still higher temperature the grain size and hence the field effect mobility are expected to rise again [26]. Koster [20] suggested that the grain size starts increasing around 850°C, but Hatalis [26] used rapid thermal annealing to find that the smallest grains are obtained at ~1100°C.…”
Section: Furnace Crystallization Of Amorphous Silicon On Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the rate of nucleation has a higher activation energy than the rate of crystal growth [20,21,22], raising the crystallization temperature above 600°C increases the number of nuclei, reduces their size, and reduces the field effect mobility [25]. Somewhere above 850°C the nucleation rate is expected to drop while the growth rate keeps rising [20], so that at still higher temperature the grain size and hence the field effect mobility are expected to rise again [26]. Koster [20] suggested that the grain size starts increasing around 850°C, but Hatalis [26] used rapid thermal annealing to find that the smallest grains are obtained at ~1100°C.…”
Section: Furnace Crystallization Of Amorphous Silicon On Steelmentioning
confidence: 99%
“…Somewhere above 850°C the nucleation rate is expected to drop while the growth rate keeps rising [20], so that at still higher temperature the grain size and hence the field effect mobility are expected to rise again [26]. Koster [20] suggested that the grain size starts increasing around 850°C, but Hatalis [26] used rapid thermal annealing to find that the smallest grains are obtained at ~1100°C. We explored crystallization temperatures of up to 950°C.…”
Section: Furnace Crystallization Of Amorphous Silicon On Steelmentioning
confidence: 99%
“…However, above some temperature the rate of nucleation begins to drop because the size of the critical nucleus grows [17]. Somewhere above 850 C the nucleation rate is expected to drop while the growth rate keeps rising [17], so that at still higher temperature the grain size and hence the field effect mobility are expected to rise again [28]. Koster [17] suggested that the grain size starts increasing around 850 C, but Hatalis [28] used rapid thermal annealing to find that the minimum grain is obtained at 1100 C. We explored crystallization temperature up to 950 C.…”
Section: B Deposition and Crystallization Of Hydrogenated Amorphous mentioning
confidence: 99%
“…What's more, the interfacial or inner defects can be also decreased using high pressure or D 2 /H 2 annealing. 8,13,[16][17][18][19][20][21][22] All aforementioned investigations were performed after the deposition of poly-Si and how the deposition conditions impact the properties of poly-Si in advanced 3D NAND memory is, however, rarely revealed. Actually, the deposition conditions indeed play an important role in modulating the properties of poly-Si and this is exactly the motivation of present work.…”
mentioning
confidence: 99%
“…23 Amorphous silicon (α-Si) was formed when the deposition temperature is less than 580°C, and it will crystalize and many grains are generated after annealing at higher temperature. 16,20,21,[24][25][26] α-Si is grown following chemical reaction formula:…”
mentioning
confidence: 99%